Design and validation of an observational instrument for goalkeepers in beach handball. - Vázquez-Diz, J. A.; Morillo-Baro, J. P.; Reigal, R. E.; Morales-Sánchez, V.; Hernández-Mendo, A. (Cuadernos de Psicología del Deporte, 2019)
Abstract : The objectives of this research were to create an instrument of observation to analyze the actions of the goalkeeper in handball beach and determine the reliability of the observers, assessing the goodness of the categories and estimating the minimum number of sessions necessary to generalize with precision. The tool ad hoc has been designed using a mixed system of field format and a system of categories, exhaustive and mutually exclusive (E/ME). It is made up of 11 criteria and 85 categories. The results have shown adequate correlation rates (=0,936) and Cohen's Kappa (=0,906). The results obtained in the Generalizability analysis are also excellent, resulting in relative G coefficients and absolute G of 0,985, in the interobserver agreement, and 0.998, for the intraobserver agreement. Overall, the results presented in this work highlight the high validity, accuracy and reliability of the observations made with the tool analyzed.